2021
DOI: 10.1111/pai.13444
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum periostin levels with clinical features in children with asthma

Abstract: Background The aim of this study was to investigate the association of serum periostin levels with clinical features in children with asthma. Methods Children with physician‐diagnosed asthma who attended regularly to an outpatient pediatric allergy and asthma center were enrolled in the study along with control subjects. Asthma severity and control status of the patients were evaluated according to the recent GINA guidelines. Results A total of 158 children (125 with asthma and 33 age‐ and sex‐matched control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
2
6
0
1
Order By: Relevance
“…Relatively higher values have been reported in the studies which have not used ELISA [12,15]. Periostin levels in the present study population were comparable to those reported in Egypt, Finland, and Turkey [18,19,21]. The study conducted by Nejman-Gryz et al in Poland enrolled children in the age group closest to the present study [20].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Relatively higher values have been reported in the studies which have not used ELISA [12,15]. Periostin levels in the present study population were comparable to those reported in Egypt, Finland, and Turkey [18,19,21]. The study conducted by Nejman-Gryz et al in Poland enrolled children in the age group closest to the present study [20].…”
Section: Discussionsupporting
confidence: 74%
“…Evidence exists regrading a positive correlation of serum periostin levels with increasing asthma severity [18,19]. Similar relationship with asthma control status has not been seen [19,22].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…severity BM Significantly higher in children with severe asthma than with mild to moderate asthma [107].…”
Section: Clinical Significance Of Serum Periostinmentioning
confidence: 89%